Investigation and Modelling of a Dual Solar Photovoltaic System for Consistent Energy Supply at Al-Brega Clinic, Libya - Mohamed Abdulhadi Faraj Hamad; Mansour Khalifa Hamad Mohammed (Journal of Scientific and Human Dimensions, 2025)
This study delineates the design and simulation of a hybrid photovoltaic (PV) system to mitigate the ongoing electricity shortages at the AL-Brega Clinic in Libya.  The system employs monocrystalline silicon cells, chosen for their superior performance in the local climate.  A thorough literature analysis on photovoltaic technologies and solar cell varieties is presented, detailing their advantages and disadvantages.  The system's performance was modeled using PVsyst software to ascertain the hourly energy output, guaranteeing it satisfies the clinic's projected annual energy requirement of 673.232 MWh, considering departmental consumption profiles.  Initial design and computations were conducted utilizing Microsoft Excel.  The modeling findings suggest an anticipated annual energy output of 3046 MWh from the planned photovoltaic system.  A cost analysis indicates levelized costs of energy (LCOE) of LYD 0.0695/kWh and LYD 0.1511/kWh for the two evaluated scenarios.  The estimated payback period, determined by the financial offset of crude oil used to produce an equivalent quantity of power, is roughly 16 years.  This study illustrates the technical and economic viability of deploying a solar photovoltaic system to bolster energy security and mitigate environmental effect for essential healthcare infrastructure in Libya.
Keywords: Hybrid Solar PV System; Off-grid Power; Healthcare Facility; PVsyst Simulation; Libya; Renewable Energy; Cost.